(untitled) (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2026)
The article substantiates the importance of an individual approach, systematicity and coherence of correctional and pedagogical work in the process of developing vocabulary. The results of the study serve to increase the effectiveness of work with children with mental retardation in the field of special pedagogy and speech therapy.